O lúdico no processo de ensino e aprendizagem na educação infantil - Lira, Janaina Pereira (Universidade Federal do Tocantins, 2019)
In fact, toys, pranks and games are specific elements of the children's world, so they are linked to the playful and the world not only of the child, but also of the adult environment. The present work has as general purpose to analyze the importance of pedagogical actions of educators involving ludicity in the teaching and learning process of early childhood education in the municipal School of Arraias-to. The methodology used to accomplish this work was the field research with the contribution of the theorists such as: Vygotsky (1989, 1997), Piaget (1998), Lopes (2016) Barbosa (2008) Moyles (2002) Among other authors who argue about the subject approached. The research had a qualitative approach, based on the application of questionnaires consisting of open and closed questions for educators of early childhood education, as well as the observation of classes taught in the class of pre II, enabling a look focused For the playful activities developed in the researched room. After the study of the data, it was concluded that the ludicity in addition to favoring the teaching and learning process, has collaborated for socialization, and the learning of rules and the conception of knowledge, being of paramount importance in the pedagogical practice, in the process of Literacy.